CRITICISM OF ELEMENTARY SCHOOL STUDENT LEARNING BOOKS IN THE LINGUISTIC THEORY STUDY - Halimatussakdiah Halimatussakdiah; Iis Suwartini; Febi Junaidi; Ramadhan Kusuma Yuda; Suryo Ediyono (JS (JURNAL SEKOLAH), 2019)
Abstract: Criticism Of Elementary School Student Learning Books In The Linguistic Theory Study. The distribution of textbooks, both printed and electronic, did not all obtain a recommendation on eligibility from the National Book Center. This paper is intended to provide criticism of the textbooks used in language learning. The analysis is done by studying the literature with the theory approach to linguistic schools. This is done to ensure that the developed textbooks do indeed contain the linguistic elements required by the curriculum. As for the book criticized "Indonesian Makes Me Smart 4". Based on analysis at the level of syntax and morphology, this book is still dominated by structural linguistic flow, and generative transformation. Various revisions need to be made so that this book meets the standards as mandated by the curriculum.Keywords: Book criticism, elementary school textbooks, linguistic theory